Selective and collective actuation in active solids - Baconnier, P.; Shohat, D.; López, C. Hernández; Coulais, C.; Démery, V.; Düring, G.; Dauchot, O. (Nature physics, 2022)
Active solids consist of elastically coupled out-of-equilibrium units performing work 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 – 13 . They are central to autonomous processes, such as locomotion, self-oscillations and rectification, in biological systems 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 – 25 , designer materials 26 and robotics 27 , 28 , 29 , 30 – 31 . Yet, the feedback mechanism between elastic and active forces as well as the possible emergence of collective behaviours in a mechanically stable elastic solid remains elusive. Here we introduce a minimal realization of an active elastic solid in which we characterize the emergence of selective and collective actuation resulting from the interplay between activity and elasticity. Polar active agents exert forces on the nodes of a two-dimensional elastic lattice. The resulting displacement field nonlinearly reorients the active agents. For a large-enough coupling, a collective oscillation of the lattice nodes around their equilibrium position emerges. Only a few elastic modes are actuated and crucially, they are not necessarily the lowest energy ones. By combining experiments with the numerical and theoretical analyses of an agent’s model, we unveil the bifurcation scenario and selection mechanism by which the collective actuation takes place. Our findings may provide a new mechanism for oscillatory dynamics in biological systems 14 , 19 , 21 , 24 and the opportunity for bona fide autonomy in metamaterials 32 , 33 . In active solids, work is performed by elastically coupled units. By studying a minimal experimental model of an active solid, actuation mechanisms resulting in a collectively oscillating displacement field that drives work cycles are now identified.